2009
DOI: 10.1088/0031-9155/54/13/013
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed fractions in ellipsoidal volumes for βradionuclides employed in internal radiotherapy

Abstract: We developed a Monte Carlo simulation in Geant4 to calculate the absorbed fractions for electrons emitted by (199)Au, (177)Lu, (131)I, (153)Sm, (186)Re and (90)Y, characterized by average energies ranging from 86 keV to 949 keV, uniformly distributed in ellipsoidal volumes of soft tissue. Code validation results with respect to reference data for doses, ranges and absorbed fractions in spheres are presented. An analytical relationship between the absorbed fraction and a 'generalized radius' is introduced in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The tumor volumes in the test mice were more ellipsoidal than spherical as illustrated in Figure 4. Amato et al (Amato et al 2009) showed that specific absorbed fractions in spheres and ellipsoids depend on the volume to surface area ratio. The specific absorbed fraction for prolated ellipsoids tend to be smaller than spheres with equivalent volumes.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor volumes in the test mice were more ellipsoidal than spherical as illustrated in Figure 4. Amato et al (Amato et al 2009) showed that specific absorbed fractions in spheres and ellipsoids depend on the volume to surface area ratio. The specific absorbed fraction for prolated ellipsoids tend to be smaller than spheres with equivalent volumes.…”
Section: Resultsmentioning
confidence: 99%
“…Such low errors are negligible in determining the effectiveness of the therapy. Based on our clinical experience and on the follow-up of the treated patients, [2][3][4] we can affirm that this approach was successfully applied to our population, without needing to differentiate patients on the disease type.…”
mentioning
confidence: 82%
“…Results of the OLINDA2 sphere model were compared with those of an analytical model for determining absorbed fractions and doses in ellipsoids filled with a uniform activity concentration [1820]. To implement the analytical model, we used the full 152 Tb emission spectrum taken from [21], which includes the β + spectrum extending up to 2.97 MeV, and all monoenergetic electrons and photons.…”
Section: Methodsmentioning
confidence: 99%